Inclusive Islamic Financing for Advancing Sustainable Intensification among Oil Palm Smallholders - Fajar Budiman; Hari Candra (Faculty of Economics, Universitas Sriwijaya, 2026)
This study develops an Islamic financing model designed for the independent oil palm smallholders in West Pasaman, Indonesia that supports sustainable intensification. Using the Research and Development (R&D) approach of design science, combining survey and interview data from 187 farmers and 15 expert informants respectively. The findings demonstrate that the economically viable sustainable intensification of oil palm smallholders in West Pasaman is challenged by a lack of adequate planting material, poor financing, and limited technical capabilities coupled with fragmented institutional coordination. However, there is considerable potential in the region for oil palm-cattle integration and for intercropping. The study proposes a financing model that integrates Islamic commercial and social finance with technical support andinstitutional collaboration. This study contributes to existing financing literature by asserting that Islamic finance is a source of capital collaboration mechanism for oil palm smallholders to shift toward more sustainable in farming intensification systems.